Take Control: A randomized trial evaluating the efficacy and safety of self‐ versus physician‐managed titration of insulin glargine 300 U/mL in patients with uncontrolled type 2 diabetes. Issue 7 (30th April 2019) - Russell‐Jones, David; Dauchy, Arnaud; Delgado, Elías; Dimitriadis, George; Frandsen, Hans A.; Popescu, Luiza; Schultes, Bernd; Strojek, Krzysztof; Bonnemaire, Mireille; Roborel de Climens, Aude; Davies, Melanie
Abstract : Aim: To compare the efficacy and safety of self‐ versus physician‐managed titration of insulin glargine 300 U/mL (Gla‐300) in people with inadequately controlled type 2 diabetes. Methods: Take Control (EudraCT number: 2015‐001626‐42) was a 24‐week, multi‐national, open‐label, controlled, two‐arm, parallel‐group study in insulin‐naïve and pre‐treated participants, randomized 1:1 to a self‐ or physician‐managed titration of Gla‐300. The fasting self‐monitored plasma glucose (SMPG) target was 4.4 to 7.2 mmol/L. The primary outcome was non‐inferiority of glycated haemoglobin (HbA1c) change from baseline to week 24. Secondary outcomes included SMPG target achievement without hypoglycaemia, hypoglycaemia incidence, adverse events and participant‐reported outcomes (PROs). Results: At week 24, the least squares (LS) mean HbA1c reduction was 0.97% (10.6 mmol/mol) and 0.84% (9.2 mmol/mol) in the self‐ and physician‐managed groups, respectively, with an LS mean difference of −0.13% [95% confidence interval −0.2619 to −0.0004] (–1.4 mmol/mol [–2.863 to –0.004]), demonstrating non‐inferiority ( P < 0.0001) and superiority ( P = 0.0247) of self‐ versus physician‐managed titration. Significantly more of the self‐ than physician‐managed group achieved SMPG target without hypoglycaemia (67% vs 58%; P = 0.0187). Overall, hypoglycaemia incidence was similar in each group. No safety concerns were reported. In both groups, similar PRO improvements were observed for distress related to diabetes disease burden and for confidence in diabetes self‐management, with even more individuals achieving a clinically relevant reduction in emotional burden and fewer individuals with high emotional burden in the self‐managed group. Conclusions: Self‐managed titration of Gla‐300 was superior to physician‐managed titration in terms of HbA1c reduction, accompanied by similar total PRO scores, with a clinically relevant reduction in emotional burden, and similar hypoglycaemia frequency.